Teplitz - Unknown:::Creator::::::::::::; Payne, Albert Henry, 1812-1902 (author):::Contributor:::::::::::: (A.H. Payne; Germany)
Engraving with images of Teplitz in Bohemia, including the Wilhelmshöhe, Belvedere, Riesenburg, Schlangenbad, Schlossplatz, and Stadtbad.